Comparison of optical features in nitrobenzene-core photonic crystal fiber with hexagonal and square lattices in the claddings - Dang Van, Trong; Le Tran, Bao Tran; Chu Van, Ben; Chu Van, Lanh (Communications in Physics, 2025)
This paper proposes two novel photonic crystal fibers (PCFs) with a nitrobenzene core, designed using hexagonal and square lattice structures. The characteristics of the PCFs were numerically analyzed in detail and compared to selecting the proposed optimal structure for supercontinuum generation. This study investigates the influence of core diameter (DC) on the characteristics of PCF. The fiber’s nonlinear properties are significantly enhanced by varying the core diameter. The hexagonal PCF structures provide flatter dispersion curves and are closer to zero dispersion than the square lattice, which is beneficial for supercontinuum generation. In contrast, the square PCF structures show higher nonlinear coefficients and lower attenuation than the corresponding hexagonal structures. Based on the simulation results, six optimized structures with all-normal and anomalous dispersion were selected to study the characteristics at the pump wavelength. Results indicate that the proposed PCFs exhibit near-zero flat dispersion, low attenuation and high nonlinearity. The selected optimal structures show potential for efficient supercontinuum generation, enabling broad and highly coherent spectra.